Use of sacubitril/valsartan in non‐compaction cardiomyopathy: a case report - Marcely Gimenes Bonatto; Rodrigo Albanez; Vera Maria Cury Salemi; Lídia Zytynski Moura (ESC Heart Failure)
Abstract The use of sacubitril/valsartan significantly reduces death or hospitalization in patients with ejection fraction < 40%. There is no study evaluating this drug effects in non‐compaction cardiomyopathy (NCCM) individuals. The aim of this article is to report a case of a patient with NCCM initially refractory to gold standard treatment and afterwards treated with sacubitril/valsartan and its improvements. This is a case report of a 48‐year‐old woman, presenting with NCCM heart failure, who had received standard guideline‐directed medical therapy for 18 months without any improvement in clinical and echocardiographic parameters. After that period, sacubitril/valsartan was initiated. After 18 months of refractory usage of guideline‐directed medical therapy, sacubitril/valsartan was started, and significant change in functional class (III to I) and important ventricular remodelling were achieved with an improvement of 29% in the ejection fraction, reduction of 7 mm in ventricular diastolic diameter, and mild to none mitral valve functional regurgitation. In this case report, sacubitril/valsartan use was associated with improvement of echocardiographic and clinical parameters in a patient with NCCM.